Starch Catabolism Revealed during Secondary Metabolite Released Under Vascular Streak Dieback Infections in Cocoa (Theobroma cacao L) - Teguh Iman Santoso; M. Miftahudin; Yohana C Sulistyaningsih; Suryo Wiyono; Fakhrusy Zakariyya (Indonesian Coffee and Cocoa Research Institute, 2021)
This study aimed to study the profile of starch content in cocoa leaf and phytoalexin production based on GC-MS analysis at several stages of VSD pathogen infection. Research was conducted on January – October 2015 at Kaliwining Experimental Field, Indonesian Coffee and Cocoa Research Institute, Jember, East Java. The research was designed based on a Completely Randomized Block Design with two factors with three replications. The first factor was clone, i.e. the resistant clone (Scavina 6) and susceptible (TSH 858) to VSD infection. The second factor was the level of O. theobromae infection, i.e. pre-infection, early infection, and late infection. Starch catabolism revealed during Vascular Streak Dieback infections in Cacao. Starch content in Sca 6 (resistant clone) in late infection decreased 24,33 % than healthy condition (no infection), however, starch content in TSH 858 (succeptible clone) in late infection decreased only 9,63 % than healthy condition (no infection). This indicated that starch catabolism rate on resistant clone was higher than susceptible clone. Some secondary metabolites releases under Vascular Streak Dieback i.e. I-limonene, eugenol and coumaran. Scavina 6 (resistant clone) had higher concentration of eugenol and coumaran than TSH 858 (susceptible clone). I-limonene compound, TSH 858 (Susceptible clone) had higher concentration than Scavina 6. I-Limonene concentration increased in lined with the severity of pathogen infection. There were an negative correlation between starch content with contentration of I-limonene (R= - 0,74), concentration of Eugenol (R= - 0,44), and contentration of Coumaran.